2020
DOI: 10.3390/ijms21020605
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of TiO2 Nanoparticles on Cisplatin Cytotoxicity in Cancer Cell Lines

Abstract: There have been many studies on improving the efficacy of cisplatin and on identifying safe compounds that can overcome multi-drug resistance (MDR) acquired by cancer cells. Our previous research showed that polyethylene glycol-modified titanium dioxide nanoparticles (TiO2 PEG NPs) affect cell membrane receptors, resulting in their aggregation, altered localization and downregulation. TiO2 PEG NPs may affect P-glycoprotein (P-gp), a membrane efflux channel involved in MDR. In this study, we investigated the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Furthermore, the effect of novel P-gp inhibitors, polyethylene glycol-modified titanium dioxide nanoparticles (TiO 2 PEG NPs), on cisplatin cytotoxicity against P-gp overexpressing HepG2 cells was examined. This study showed that increased cisplatin cytotoxicity was associated with downregulation of the expression of P-gp in HepG2 cells by TiO 2 PEG NPs [35].…”
Section: Enhanced Efflux Of Drugsmentioning
confidence: 72%
See 1 more Smart Citation
“…Furthermore, the effect of novel P-gp inhibitors, polyethylene glycol-modified titanium dioxide nanoparticles (TiO 2 PEG NPs), on cisplatin cytotoxicity against P-gp overexpressing HepG2 cells was examined. This study showed that increased cisplatin cytotoxicity was associated with downregulation of the expression of P-gp in HepG2 cells by TiO 2 PEG NPs [35].…”
Section: Enhanced Efflux Of Drugsmentioning
confidence: 72%
“…This includes ERCC1-XPF inhibitors (E-X PPI2, E-X AS7, compound 13, and compound B5), RPA inhibitors (TDRL-551, SMI MCI13E, and TDRL-55 derivatives), ATR kinase inhibitors (VX-970 and AZD6738), DNA-PKcs inhibitors (NU7026, NU7441, and AZD7648), HR inhibitors (B02 compound), and TLS inhibitors (JH-RE-06, T2AA, and compounds 4 and 5) [88,[91][92][93][94][95][98][99][100][101][102][103][104][105][106]. Other substances, such as taxifolin, sitravatinib, cinobufagin, crown ethers, ascorbic acid, TTM, so-PXA, mPEG glycine-quinidine conjugate, and TiO 2 PEG NPs that have been designed to block efflux of drugs outside the cancer cells are known as P-gp inhibitors [18,[28][29][30][31][32][33][34][35]. Another group involves drugs that are capable of increasing metabolism of xenobiotics in tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Oridonin-entrapped galactosylated chitosan nanoparticles (ORI-GC-NP) exhibited IC50 values of 31.07 and 26.59 µM against MCF-7 cells and HepG2.cells, respectively 45 . Furthermore, a study reported that IC50 values of polyethylene glycol-modified titanium dioxide nanoparticles (TiO2 PEG NPs) against HepG2 and A431 cells were 12.00 and 6.00 µg/mL, respectively 46 .…”
Section: Resultsmentioning
confidence: 99%
“…The IC 50 value of the most commonly used cancer drug, cisplatin has been reported to be between 6 mg mL À1 to 9 mg mL À1 (20 to 30 mM) for A431 skin cancer cells and 6 mg mL À1 (20 mM) for MCF-7 breast cancer cells. [45][46][47] It is more than two fold higher than the IC 50 values observed for carboranyl glycoconjugates 15 and 17 (with three glucose and galactose units with o-carborane). The IC 50 of cisplatin is more than three fold higher than the IC 50 values observed for carboranyl glycoconjugates 19 and 21 (with three glucose and galactose units with o-carborane).…”
Section: In Vitro Cytotoxicity Testmentioning
confidence: 99%